Evaluation of spiritual health level and its related factors in the students of Sanandaj Universities, 2015 - Mahnaz Sayyadi (روانشناسی و روانپزشکی شناخت, 2019)
Introduction: Spirituality is the most important aspect of human existentialism. This dimension is considered as a strong force in the center of life for more than one-third of the people worldwide. Spirituality is linked to health, a sense of goodness and recovery, and a factor in the continuation of life, finding its meaning and purpose. Aim: This study aimed to determine spiritual health level and its related factors in the students of Sanandaj universities in 2015. Method: The present study was a cross-sectional. The study population, were students of Kurdistan University, Islamic Azad University of Sanandaj and Kurdistan University of Medical Sciences. Five hundred persons of them were selected and studied using One-stage cluster sampling method. A two-part questionnaire including demographic characteristics and 20 questions about spiritual health was used. The data were analyzed using SPSS 20. Results: The mean score of the belief system, intellectual, moral and life style of spiritual health were 25.78±3.95, 25.54±4.37, 22.97±4.65 and 23.04±4.75, respectively. The mean overall score of spiritual health was 96.33±14.92. The score was at the high level of health. There was a statistically significant difference between degrees (p<0.001), university (p<0.001), group study (p=0.007), pray and fasting (p<0.001) with mean total score of spiritual health. Conclusion: In the dimensions of the ethical system and lifestyle, the mean score of students was lower than the other dimensions, which could be somewhat alarming. It is recommended that the cultural planners of the universities Pay close attention and apply appropriate training.